Temporal changes in technical and physical performances during a small-sided game in elite youth soccer players - Moreira, A.; Saldanha Aoki, M.; Carling, C.; Rodrigues Lopes, R. A.; Schultz de Arruda, A. F.; Lima, M.; Correa, U. C.; Bradley, P. S. (Asian Journal of Sports Medicine, 2016)
Background: There have been claims that small-sided games (SSG) may generate an appropriate environment to develop youth players` technical performance associated to game-related problem solving. However, the temporal change in technical performance parameters of youth players during SSG is still unknown.